MANAGEMENT OF A COMPANY’S CURRENT ASSETS IN ENSURING SUSTAINABLE ECONOMIC DEVELOPMENT - Левковець, Наталія; Бабич, Людмила (SWorldJournal, 2025)
The article explores the management of current assets in enterprises, emphasizing it as a crucial factor in ensuring their sustainable economic development. It examines the role of current assets in maintaining financial stability, solvency, and competiti